The impact of internal marketing on job satisfaction, organizational commitment, and employee loyalty - Pratama, Rizky Ananda; Anindita, Rina (Jurnal Ekonomi dan Bisnis, 2025)
Internal marketing is critical in influencing job satisfaction and organizational commitment.  Accordingly, this research analyzes the impact of internal marketing on job satisfaction, organizational commitment, and employee loyalty at AirNav Indonesia Denpasar Branch. Using the Structural Equation Modeling (SEM) analysis method, we analyzed the data from 125 respondents of the company’s operational employees. Our findings demonstrate that internal marketing affects job satisfaction and organizational commitment, not employee loyalty. The indirect effect of internal marketing on employee loyalty is mediated by job satisfaction and organizational commitment. Meanwhile, job satisfaction positively affects organizational commitment and employee loyalty. Our study informs AirNav Indonesia or similar companies of the importance of internal marketing to improve employee performance and loyalty through greater job satisfaction and commitment.